2019
DOI: 10.1016/j.bbagen.2019.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial garlic-derived diallyl polysulfanes: Interactions with biological thiols in Bacillus subtilis

Abstract: Background: Diallylpolysulfanes are the key constituents of garlic oils, known to exhibit broad spectrum anticancer and antimicrobial activity. Studies in vitro, and in mammalian cells, have shown they react, via thiolpolysulfane exchange, with their major low molecular weight thiol, glutathione. However, there are no detailed reports of diallylpolysulfane effects on other common thiol metabolites (cysteine and coenzyme A) or major thiol cofactors (e.g. bacillithiol) that many Gram positive bacteria produce in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…In recent years, researchers have used the hydrolysis and other techniques to prepare antihypertensive peptides from food-derived proteins (Tu, Cheng, Lu, & Du, 2018). Many studies revealed that garlic has antitumor (Song & Milner, 2001), antimicrobial (Arbach et al, 2019;Horita et al, 2016), antioxidant (Chen & Huang, 2019), reducing blood lipid (Shabani, Sayemiri, & Mohammadpour, 2019), anticardiovascular disease (Amor et al, 2019), and antidiabetic activities. Garlic (Allium sativum L.) belongs to the genus Allium of the Liliaceae family, which has been widely planted all over the world, mainly for cooking and medicinal applications (Ebrahimi Pure, Ghods Mofidi, Keyghobadi, & Ebrahimi Pure, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have used the hydrolysis and other techniques to prepare antihypertensive peptides from food-derived proteins (Tu, Cheng, Lu, & Du, 2018). Many studies revealed that garlic has antitumor (Song & Milner, 2001), antimicrobial (Arbach et al, 2019;Horita et al, 2016), antioxidant (Chen & Huang, 2019), reducing blood lipid (Shabani, Sayemiri, & Mohammadpour, 2019), anticardiovascular disease (Amor et al, 2019), and antidiabetic activities. Garlic (Allium sativum L.) belongs to the genus Allium of the Liliaceae family, which has been widely planted all over the world, mainly for cooking and medicinal applications (Ebrahimi Pure, Ghods Mofidi, Keyghobadi, & Ebrahimi Pure, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Garlic (Allium sativum) has been historically used as a medicinal plant for the treatment of infectious diseases, such as tuberculosis, due to the production of volatile reactive sulfur compounds. The main thiol-reactive sulfur ingredient of garlic is the diallyl thiosulfinate (allicin), which acts as antimicrobial and inhibits the growth and survival of several important human pathogens, including multi-drug resistant bacteria, fungi, and parasites [1][2][3][4][5][6][7][8][9]. Upon garlic tissue damage, the enzyme cysteine-S-lyase alliinase is released from the vacuole into the cytosol to synthesize allyl sulfenic acid and dehydroalanine from the odor-less precursor alliin.…”
Section: Introductionmentioning
confidence: 99%
“…Allicin and diallyl polysulfanes DAS2-6 showed different extents of thiol-reactivity and microbicidal effects, with DAS4-6 and allicin being more potent antimicrobials compared to diallyl diand trisulfides (DAS2-3) [3,9]. The effects of garlic polysulfanes DAS2-6 were compared on the growth and the minimal inhibitory concentration (MIC) of Bacillus subtilis, Helicobacter pylori, Staphylococcus aureus, and fungi, which showed that the antimicrobial activity of polysulfanes increases with longer sulfur chain length [9,[15][16][17]. However, the stability of DAS5-6 is also strongly decreased compared to DAS2-4, and polysulfanes of longer chain length tend to rearrange to a mix of shorter polysulfanes when incubated with glutathione (GSH) in vitro [9,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations